Respuesta :
ANSWER:
14y - 42x
STEP-BY-STEP EXPLANATION:
Let's first write down the problem we will be solving.
= - 7 ( 6x - 2y )
To use the distributive law to remove the parantheses, we need to multiply each number inside the parentheses with the number in front of the parantheses.
= - ( 7 × 6x ) - ( 7 × - 2y )
Then we write down the product of each multiplication and put it together to make our final expression.
= - ( 42x ) - ( - 14y )
= - 42x + 14y
If possible, it is always better to ensure that the expression begins with a positive rather than a negative symbol. To do this, you simply place the positive number at the front of the expression and the negative number after it.
= 14y - 42x
14y - 42x
STEP-BY-STEP EXPLANATION:
Let's first write down the problem we will be solving.
= - 7 ( 6x - 2y )
To use the distributive law to remove the parantheses, we need to multiply each number inside the parentheses with the number in front of the parantheses.
= - ( 7 × 6x ) - ( 7 × - 2y )
Then we write down the product of each multiplication and put it together to make our final expression.
= - ( 42x ) - ( - 14y )
= - 42x + 14y
If possible, it is always better to ensure that the expression begins with a positive rather than a negative symbol. To do this, you simply place the positive number at the front of the expression and the negative number after it.
= 14y - 42x